Effect of Centaurea pullata Methanolic Extract on the Growth of Portulaca oleracea - Wasi Ullah Khan; Rahmat Ali Khan; Safir Ullah Khan (Journal of Basic & Applied Sciences, 2017)
Phytotoxicity or allelopathy means poisonous results by a composite onplantgrowth, composites may be trace metals, pesticides salinity or phytotoxins. Some of the medicinal plants have phytotoxic activities which inhibit the growth of weeds and unwanted plants which are not of our desire. The present study is aimed to investigate the phytotoxic assessment of Centaurea pullata methanolic extract (CPME) roots. Dried plant were ground and extracted with methanol to prepare methanol crude extract. In-vitro phytotoxicity activity was conducted using these methanolic extracts as per standard procedures. The inhibitory effect of Centaurea pullata extract is tested on stalk and root of Portulaca oleracea and using four concentrations (3, 1.5, 0.75 and 0.37mg/ml) of plant extract and distal water in control. The result is noted on 5th and 10th days. The results obtained from these experiments showed that the crude methanolic extract of Centaurea pullata slightly inhibits the roots and shoots of Portulaca oleracea seeds as compared to the control plate which was not treated by the above mentioned sample extracts shown in Figures as. From the results obtained that, Phytotoxicity activity of Centaurea pullata methanolic extract showed non-significant results. Purification and in vivo studies of these plant are required for further verification.